Zinc-nickel single-flow battery slurry-pulling positive plate and preparation method thereof, zinc-nickel single-flow battery and zinc-nickel single-flow battery stack

The foam nickel positive electrode sheet prepared by the slurry drawing process in the zinc-nickel single-flow battery solves the problems of low positive electrode capacity and high production cost in the traditional zinc-nickel single-flow battery, and achieves high capacity, high activity and low cost effects.

CN120221675APending Publication Date: 2025-06-27BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411054362.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2025-06-27

Smart Images

  • Figure CN120221675A_ABST
    Figure CN120221675A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage, and provides a zinc-nickel single-flow battery slurry-pulling positive plate and a preparation method thereof, a zinc-nickel single-flow battery and a zinc-nickel single-flow battery stack.The zinc-nickel single-flow battery slurry-pulling positive plate comprises a foamed nickel substrate and a positive active compound distributed in the foamed nickel substrate, the positive electrode active compound comprises a positive electrode active substance, a conductive agent, potassium polyacrylate and an adhesive, and the content of the potassium polyacrylate in the positive electrode active compound is 0.01-4.00 wt%. According to the zinc-nickel single-flow battery stack slurry-pulling positive plate provided by the invention, industrial batch production of the zinc-nickel single-flow battery stack slurry-pulling positive plate with the width of 500mm is realized, the production process is rigorous, the consistency is good, and the zinc-nickel single-flow battery stack slurry-pulling positive plate has the advantages of high capacity, high activity, high stability and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage, and particularly relates to a zinc-nickel single-flow battery pasted positive electrode sheet, a preparation method thereof, a zinc-nickel single-flow battery, and a zinc-nickel single-flow battery stack. Background Art

[0002] In the field of large-scale energy storage technologies, electrochemical energy storage technologies are continuously improving. As a supporting technology for the national energy strategy, new energy storage is transforming from the initial commercial stage to large-scale development. As a new energy storage battery technology, the zinc-nickel single-flow battery uses the same electrolyte for both the positive and negative electrodes, and does not require the use of expensive ion exchange membranes. The battery materials are relatively inexpensive, and its unique advantages make it have good application prospects.

[0003] The preparation of nickel positive electrodes is mainly divided into sintered type and foam type. In the early stage, sintering technology was usually used for nickel positive electrodes. The nickel hydroxide active material of the sintered nickel positive electrode can be in close contact with the current collector, having a relatively high specific surface area and excellent electrochemical performance. However, the sintered positive electrode has a large volume and a low active material content, resulting in a low energy density, and the complex electrode manufacturing process has a high cost; the foam nickel positive electrode avoids the use of a bulky sintered nickel substrate, thus significantly increasing the active material content in the positive electrode and has become the most widely used nickel electrode form at present. The foam pasted positive electrode is usually used in zinc-nickel solid-state batteries or nickel-metal hydride batteries, and the active area of the electrode is small, while the traditional zinc-nickel single-flow battery still uses the sintering process to prepare the nickel positive electrode. The main reason is that the flowing electrolyte in the flow battery puts more stringent requirements on the adhesion of the nickel positive electrode active material, and the flushing of the electrolyte is more likely to cause the shedding of the adhered nickel positive electrode active material, resulting in a loss of battery capacity. Summary of the Invention

[0004] To achieve large-scale energy storage and meet the requirements of high capacity and high active area for energy storage, it is of great significance to develop a pasting process applicable to zinc-nickel single-flow batteries, that is, it is necessary to prepare a foam nickel positive electrode with a high active area and a stable structure. At the same time, the preparation process of the foam nickel positive electrode is simple, with lower energy consumption and high production efficiency.

[0005] The purpose of the present invention is to overcome the problems of low capacity and high production cost of the positive electrode sheet of traditional zinc-nickel single-flow batteries, and to provide a zinc-nickel single-flow battery pasted positive electrode sheet, a preparation method thereof, a zinc-nickel single-flow battery, and a zinc-nickel single-flow battery stack. The positive electrode sheet has the advantages of high capacity, high activity, high stability, and low cost.

[0006] The zinc-nickel single-flow battery pasted positive electrode sheet provided by the present invention realizes the industrial batch production of a zinc-nickel single-flow battery pasted positive electrode sheet with a width of 500 mm. The production process is rigorous and has good consistency. Compared with the positive electrode of the traditional sintered zinc-nickel single-flow battery, it has low energy consumption, high production efficiency, and at the same time has the advantages of high capacity, high activity, and high stability.

[0007] The positive electrode paste prepared by the present invention has good fluidity and high viscosity. Through the four-roll sizing device, a high loading of the positive electrode active material is achieved, improving the positive electrode capacity. Pre-pressing of the nickel foam can improve the uniformity of the positive electrode drawing, adjusting the drawing speed and drying in multiple temperature zones enables the solvent to be dried at a relatively fast speed, while ensuring the yield and production efficiency of the positive electrode sheet. An appropriate rolling thickness improves the internal contact resistance and AC impedance of the positive electrode sheet, and also ensures sufficient porosity of the positive electrode sheet to achieve good ion conduction within the pores.

[0008] To achieve the above object, on the one hand, the present invention provides a drawn positive electrode sheet for a zinc-nickel single flow battery, comprising a nickel foam substrate and a positive electrode active composite distributed in the nickel foam substrate. The positive electrode active composite comprises a positive electrode active material, a conductive agent, potassium polyacrylate, and a binder. Among them, in the positive electrode active composite, the content of potassium polyacrylate is 0.01 - 4.00 wt%.

[0009] On the second aspect, the present invention provides a method for preparing a drawn positive electrode sheet for a zinc-nickel single flow battery, the method comprising: formulating the positive electrode active composite, mixing the positive electrode slurry, drawing on the nickel foam substrate, drying, rolling, and slicing. The formulation of the positive electrode active composite contains a positive electrode active material, a conductive agent, potassium polyacrylate, and a binder. Among them, in the positive electrode active composite, the content of potassium polyacrylate is 0.01 - 4.00 wt%.

[0010] On the third aspect, the present invention provides a zinc-nickel single flow battery, the positive electrode being the drawn positive electrode sheet for a zinc-nickel single flow battery of the present invention. The positive electrode sheet comprises a nickel foam substrate and a positive electrode active composite distributed in the nickel foam substrate. The positive electrode active composite comprises a positive electrode active material, a conductive agent, potassium polyacrylate, and a binder. Among them, in the positive electrode active composite, the content of potassium polyacrylate is 0.01 - 4.00 wt%.

[0011] On the fourth aspect, the present invention provides a zinc-nickel single flow battery stack, the zinc-nickel single flow battery stack being assembled with 5 - 40 zinc-nickel single flow batteries of the present invention, and the power pump being selected from magnetic pumps.

[0012] The drawn positive electrode sheet for a zinc-nickel single flow battery provided by the present invention realizes the industrial mass production of a drawn positive electrode sheet for a zinc-nickel single flow battery with a width of 500 mm. The production process is rigorous and the consistency is good. Description of the Drawings

[0013] Figure 1 is the mass specific capacity-voltage relationship diagram of the zinc-nickel single flow battery stack in Example 1 at a current density of 35 mA cm -2 Current density;

[0014] Figure 2is the cycle efficiency diagram of the zinc-nickel single-flow battery stack of Example 1 at a current density of 35 mA cm -2 ;

[0015] Figure 3 is the cycle efficiency diagram of the zinc-nickel single-flow battery stack of Comparative Example 1 at a current density of 35 mA cm -2 ; Detailed implementation manners

[0016] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0017] The present invention provides a zinc-nickel single-flow battery pasted positive electrode sheet, which includes a nickel foam substrate and a positive electrode active composite distributed in the nickel foam substrate. The positive electrode active composite includes a positive electrode active material, a conductive agent, potassium polyacrylate, and an adhesive. Among them, in the positive electrode active composite, the content of potassium polyacrylate is 0.01-4.00 wt%.

[0018] The zinc-nickel single-flow battery pasted positive electrode sheet provided by the present invention has low energy consumption and high production efficiency compared with the positive electrode of the traditional sintered zinc-nickel single-flow battery, and at the same time has the advantages of high capacity, high activity, and high stability.

[0019] In the present invention, the optional range of the positive electrode active material is relatively wide, and common positive electrode active materials can be used in the present invention. The following is a demonstration, but it does not limit the scope of the present invention. For example, it is selected from one or more of nickel hydroxide, nickel oxide, nickel hydroxide doped with zinc and / or cobalt elements.

[0020] In the present invention, the optional range of the conductive agent is relatively wide, and common conductive agents can be used in the present invention. The following is a demonstration, but it does not limit the scope of the present invention. For example, the conductive agent is selected from one or more of superconducting carbon black, carbon nanotubes, graphite powder, and graphene.

[0021] In the present invention, the optional range of the adhesive is relatively wide, and common adhesives can be used in the present invention. The following is a demonstration, but it does not limit the scope of the present invention. For example, the adhesive is selected from one or more of polytetrafluoroethylene, gum arabic, and acrylate. The polytetrafluoroethylene and gum arabic used in the present invention are commercially available products, and commonly used ones include 60 wt% polytetrafluoroethylene emulsion, 10 wt% gum arabic solution, etc.

[0022] In the present invention, the positive electrode sheets having the foregoing composition and content can all achieve the object of the present invention, and the optional range of the width of the positive electrode sheet is relatively wide. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the width of the positive electrode sheet can reach 500 mm.

[0023] In the present invention, the optional range of the thickness of the positive electrode sheet is relatively wide. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the thickness of the positive electrode sheet is 0.5 to 1.0 mm. By adopting the foregoing technical solution, it has the advantages of high positive electrode stability and long service life.

[0024] In the present invention, in the positive electrode sheet, the optional range of the loading amount of the positive electrode active material is relatively wide. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the positive electrode sheet, the loading amount of the positive electrode active material is 0.10 to 0.25 g cm -2 . By adopting the foregoing technical solution, the positive electrode sheet has high capacity and high activity.

[0025] In the present invention, the optional range of the number average molecular weight of potassium polyacrylate is relatively wide. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the number average molecular weight of the potassium polyacrylate is 5000 to 10000000. By adopting the foregoing technical solution, the problem of framework collapse in the application of sodium carboxymethyl cellulose in the zinc-nickel single-flow battery using the traditional foam nickel positive electrode is avoided; and potassium polyacrylate has excellent water absorption and water retention properties, can significantly increase the slurry viscosity to maintain the slurry stability, and improve the consistency of the positive electrode preparation.

[0026] According to a preferred embodiment of the present invention, the potassium polyacrylate includes potassium polyacrylate with a number average molecular weight of 10000 to 100000 and potassium polyacrylate with a number average molecular weight of 500000 to 5000000. Based on the total weight of the potassium polyacrylate, the mass content of each is not less than 15 wt%, and preferably the content of each is 20 to 80 wt%. By adopting the foregoing technical solution, the positive electrode sheet has good consistency and high stability.

[0027] In the present invention, as long as the object of the present invention can be achieved, in the positive electrode active complex, the optional range of the content of potassium polyacrylate is relatively wide. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the positive electrode active complex, the content of potassium polyacrylate is 0.05 to 4.00 wt%, such as 0.08 wt%, 0.10 wt%, 0.30 wt%, 0.80 wt%, 1.00 wt%, 1.50 wt%, 2.00 wt%, 2.50 wt%, 3.00 wt%, 3.50 wt%. By adopting the foregoing technical solution, the positive electrode sheet has good consistency and high stability.

[0028] In the present invention, as long as the object of the present invention can be achieved, there is no special requirement for the content of the positive electrode active material in the positive electrode active complex. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the positive electrode active complex, the content of the positive electrode active material is 60-95 wt%, preferably 65-90 wt%.

[0029] In the present invention, as long as the object of the present invention can be achieved, there is no special requirement for the content of the conductive agent in the positive electrode active complex. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the positive electrode active complex, the content of the conductive agent is 3-20 wt%, preferably 5-16 wt%.

[0030] In the present invention, as long as the object of the present invention can be achieved, there is no special requirement for the content of the binder in the positive electrode active complex. According to a preferred embodiment of the present invention, in the positive electrode active complex, the content of the binder is 1-10 wt%, preferably 2-8 wt%.

[0031] In the present invention, the function of the positive electrode active additive is to improve the conductivity of positive electrode active materials such as Ni(OH)2, increase the electron transport channels and improve the electron transport rate, and reduce the polarization resistance; inhibit the volume expansion of the positive electrode and extend the cycle life. According to a preferred embodiment of the present invention, the positive electrode active complex contains a positive electrode active additive. The optional range of the additive is relatively wide. A demonstration of an embodiment is given below, but it does not limit the scope of the present invention. For example, the positive electrode active additive is selected from one or more of cobalt hydroxide, cobaltous oxide, manganese dioxide, and zinc powder, preferably cobalt hydroxide and zinc powder. By adopting the foregoing technical solution, the positive electrode has good conductivity and a long cycle life.

[0032] In the present invention, as long as the object of the present invention can be achieved, there is no special requirement for the content of the positive electrode active additive in the positive electrode active complex. According to a preferred embodiment of the present invention, in the positive electrode active complex, the content of the positive electrode active additive is 1-15 wt%, preferably 2-11 wt%. By adopting the foregoing technical solution, the positive electrode has good conductivity and a long cycle life.

[0033] The present invention provides a method for preparing a zinc-nickel single-flow battery slurring positive electrode sheet, including: positive electrode active complex batching, positive electrode pulping and mixing, slurring on a nickel foam substrate, drying, rolling, and slicing. The positive electrode active complex batching contains a positive electrode active material, a conductive agent, potassium polyacrylate, and a binder. Among them, in the positive electrode active complex, the content of potassium polyacrylate is 0.01-4.00 wt%.

[0034] In the present invention, as long as the object of the present invention can be achieved, the content range of potassium polyacrylate in the positive electrode active composite formulation is relatively wide. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the positive electrode active composite formulation, the content of potassium polyacrylate is 0.05-4.00 wt%, such as 0.08 wt%, 0.10 wt%, 0.30 wt%, 0.80 wt%, 1.00 wt%, 1.50 wt%, 2.00 wt%, 2.50 wt%, 3.00 wt%, 3.50 wt%. By adopting the foregoing technical solution, the positive electrode sheets prepared have good consistency and high stability.

[0035] In the present invention, as long as the object of the present invention can be achieved, there are no special requirements for the content of the positive electrode active material in the positive electrode active composite formulation. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the positive electrode active composite formulation, the content of the positive electrode active material is 60-95 wt%, preferably 65-90 wt%.

[0036] In the present invention, as long as the object of the present invention can be achieved, there are no special requirements for the content of the conductive agent in the positive electrode active composite formulation. The following is a demonstration, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the positive electrode active composite formulation, the content of the conductive agent is 3-20 wt%, preferably 5-16 wt%.

[0037] In the present invention, as long as the object of the present invention can be achieved, there are no special requirements for the content of the binder in the positive electrode active composite formulation. According to a preferred embodiment of the present invention, in the positive electrode active composite formulation, the content of the binder is 1-10 wt%, preferably 2-8 wt%.

[0038] In the present invention, the function of the positive electrode active additive is to improve the conductivity of positive electrode active materials such as Ni(OH)2, increase the electron transport channels and improve the electron transport rate, and reduce the polarization resistance; inhibit the volume expansion of the positive electrode and extend the cycle life. According to a preferred embodiment of the present invention, the positive electrode active composite formulation contains a positive electrode active additive, and the optional range of the additive is relatively wide. A demonstration of an embodiment is given, but it does not limit the scope of the present invention. For example, the positive electrode active additive is selected from one or more of cobalt hydroxide, cobaltous oxide, manganese dioxide, and zinc powder, preferably cobalt hydroxide and zinc powder. By adopting the foregoing technical solution, the positive electrode has good conductivity and a long cycle life.

[0039] In the present invention, as long as the object of the present invention can be achieved, there is no special requirement for the content of the positive electrode active additive in the positive electrode active composite formulation. According to a preferred embodiment of the present invention, in the positive electrode active composite formulation, the content of the positive electrode active additive is 1 to 15 wt%, preferably 2 to 11 wt%. By adopting the foregoing technical solution, the positive electrode has good conductivity and a long cycle life.

[0040] In the present invention, as long as the object of the present invention can be achieved, there is no special requirement for the positive electrode pulping and mixing process. A demonstration of an embodiment is given, but the scope of the present invention is not limited thereby. According to a preferred embodiment of the present invention, the positive electrode pulping and mixing process includes: adding a positive electrode active composite to a solvent and mixing evenly to obtain a positive electrode slurry.

[0041] According to a preferred embodiment of the present invention, the positive electrode pulping and mixing process includes: mixing evenly a positive electrode active material, a conductive agent, potassium polyacrylate and a binder in a solvent in proportion.

[0042] More specifically, the positive electrode pulping and mixing process includes: adding the binder to the solvent and stirring evenly first, then adding potassium polyacrylate and stirring evenly, and finally adding the evenly mixed positive electrode active material, conductive agent and additive powder and stirring evenly.

[0043] In the present invention, during the positive electrode pulping and mixing process, there is no special requirement for the stirring time. A demonstration of an embodiment is given, but the scope of the present invention is not limited thereby. For example, adding the binder to the solvent and stirring evenly for 10 to 150 min to prepare a uniform emulsion, and the time is preferably 10 to 100 min; then adding potassium polyacrylate and stirring for 30 min to 180 min to prepare a gel-like viscous liquid, and the time is preferably 30 to 120 min; finally, stirring the positive electrode active material, conductive agent and additive powder evenly and adding them to the aforementioned gel-like viscous liquid, and stirring for 60 to 180 min, preferably 90 to 180 min.

[0044] In the present invention, there is no special requirement for the equipment used to prepare the slurry, and common stirring equipment can be used in the present invention. For example, a vacuum stirrer is used to prepare the slurry. In the present invention, for the positive electrode slurry, the optional range of the content of the positive electrode active composite and the solvent is relatively wide. A demonstration of an embodiment is given, but the scope of the present invention is not limited thereby. According to a preferred embodiment of the present invention, in the positive electrode slurry, the mass concentration of the positive electrode active composite is 40 to 80 wt%, and the mass concentration of the solvent is 20 to 60 wt%. By adopting the foregoing technical solution, there are advantages such as uniform dispersion of the slurry and good consistency.

[0045] In the present invention, the solvent used in the process of preparing the positive electrode slurry has a relatively wide optional range. One embodiment is demonstrated by way of example, but this does not limit the scope of the present invention. For example, the solvent includes one or more of water, ethanol, and isopropyl alcohol. According to a preferred embodiment of the present invention, the solvent is a mixed solution of isopropyl alcohol and water, and the amount of isopropyl alcohol is 5-15 wt% based on the total weight of the solvent. By adopting the foregoing technical solution, there are advantages such as uniform dispersion of the slurry and good consistency.

[0046] In the present invention, the viscosity of the positive electrode slurry has a relatively wide optional range. One embodiment is demonstrated by way of example, but this does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the viscosity of the positive electrode slurry is 3000-20000 mPa s. By adopting the foregoing technical solution, there are advantages such as good stability of the slurry and good consistency of the prepared positive electrode.

[0047] In the present invention, there are no special requirements for the process of drawing the slurry on the nickel foam substrate, and common drawing methods can be used in the present invention. One embodiment is demonstrated by way of example, but this does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the process of drawing the slurry on the nickel foam substrate includes: unwinding, pre-pressing, and drawing the slurry. In the present invention, the processes of drawing the slurry on the nickel foam substrate and rolling are well-known to those skilled in the art. By adopting the foregoing technical solution, there are advantages such as simple positive electrode preparation process, good consistency, and high production efficiency.

[0048] In the present invention, as long as the object of the present invention can be achieved, there are no special requirements for the nickel foam coil used in the unwinding process. For example, a nickel foam coil with a width not exceeding 500 mm and a thickness not less than 1.6 mm is placed in the unwinding process.

[0049] In the present invention, the pre-pressed thickness of the nickel foam substrate has a relatively wide optional range. One embodiment is demonstrated by way of example, but this does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the pre-pressed thickness of the nickel foam substrate is set to 1.0-1.5 mm. By adopting the foregoing technical solution, there is an advantage of good uniformity in drawing the slurry on the positive electrode.

[0050] In the present invention, there are no special requirements for the method of drawing the slurry, and common drawing methods can be used in the present invention. One embodiment is demonstrated by way of example, but this does not limit the scope of the present invention. According to a preferred embodiment of the present invention, four-roll sizing is used for drawing the slurry. Generally, after the nickel foam is pre-pressed, it enters the hopper, and the slurry is coated into the nickel foam substrate through a four-roll sizing device in the hopper. The drawing speed and multi-temperature zone drying are adjusted to dry the solvent at a relatively fast speed, and the dried electrode sheet is rolled and sliced into a suitable thickness. By adopting the foregoing technical solution, there are advantages such as high loading of the positive electrode active material and high capacity.

[0051] Specifically, the positive electrode slurry is pumped by a diaphragm pump and added to the slurry drawing hopper to start slurry drawing. Four-roll sizing is used for the hopper slurry drawing, and the diaphragm pump is automatically sized through electrical control to ensure a constant slurry liquid level in the slurry drawing hopper. Adopting the foregoing technical solution has the advantage of good positive electrode consistency.

[0052] In the present invention, the optional range of the slurry drawing speed is relatively wide. One embodiment is demonstrated, but this does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the slurry drawing speed is set to 0.5 - 3 m / s. -1 Adopting the foregoing technical solution has the advantage of high production efficiency.

[0053] In the present invention, as long as the object of the present invention can be achieved, the optional range of the drying temperature is relatively wide. One embodiment is demonstrated, but this does not limit the scope of the present invention. According to a preferred embodiment of the present invention, during the drying process: four-zone drying is set, and the temperatures of the four-zone drying are 70 - 90 °C, 90 - 110 °C, 100 - 130 °C, and 80 - 120 °C respectively. Adopting the foregoing technical solution has the advantages of high production efficiency and good positive electrode performance.

[0054] In the present invention, the purpose of rolling is to ensure the stability of the positive electrode structure during the cycle of the prepared positive electrode. According to a preferred embodiment of the present invention, after rolling, the thickness of the positive electrode sheet is 0.5 - 1.0 mm.

[0055] The positive electrode slurry prepared by the present invention has good fluidity and high viscosity. Through the four-roll sizing device, a high loading of the positive electrode active material is achieved, and the positive electrode capacity is increased. The pre-pressing of nickel foam can improve the uniformity of the positive electrode slurry drawing, and adjusting the slurry drawing speed and multi-zone drying realizes the drying of the solvent at a relatively fast speed, while ensuring the yield and production efficiency of the positive electrode sheet. The appropriate rolling thickness improves the contact internal resistance and AC impedance of the positive electrode sheet, and also ensures sufficient porosity of the positive electrode sheet to achieve good ion conduction in the pores.

[0056] The present invention provides a zinc-nickel single-flow battery slurry-drawn positive electrode sheet prepared by the method described in the present invention.

[0057] The zinc-nickel single-flow battery slurry-drawn positive electrode sheet provided by the present invention realizes the industrialized batch production of a zinc-nickel single-flow battery slurry-drawn positive electrode sheet with a width of 500 mm. The production process is rigorous and has good consistency. Compared with the positive electrode of the traditional sintered zinc-nickel single-flow battery, it has low energy consumption and high production efficiency, and at the same time has the advantages of high capacity, high activity, and high stability.

[0058] The present invention provides a zinc-nickel single-flow battery. The positive electrode is the drawn positive electrode sheet of the zinc-nickel single-flow battery of the present invention. The positive electrode sheet includes a nickel foam substrate and a positive electrode active composite distributed in the nickel foam substrate. The positive electrode active composite includes a positive electrode active material, a conductive agent, potassium polyacrylate, and an adhesive. Among them, in the positive electrode active composite, the content of potassium polyacrylate is 0.01-4.00 wt%.

[0059] In the present invention, there are no special requirements for the preparation of the zinc-nickel single-flow battery, and it can be prepared according to the existing technology. One implementation mode is demonstrated, but the scope of the present invention is not limited thereby. For example, the negative electrode is selected from one or more of carbon felt, graphite felt, carbon cloth, or zinc sheet, and the electrolyte is a 7-10 M potassium hydroxide solution dissolved with 0.5-1 M zinc oxide. The liquid storage tank, pump, and pipeline in the zinc-nickel single-flow battery can be selected according to the existing technology, which does not affect the performance of the zinc-nickel single-flow battery of the present invention, and the present invention will not elaborate.

[0060] The present invention provides a zinc-nickel single-flow battery stack, which is assembled in series by 5-40 zinc-nickel single-flow batteries of the present invention.

[0061] In the present invention, the series assembly of the zinc-nickel single-flow battery stack is well-known to those skilled in the art and can be assembled according to the existing technology, which does not affect the performance of the zinc-nickel single-flow battery stack of the present invention, and the present invention will not elaborate.

[0062] Example 1

[0063] Use a vacuum mixer to prepare the slurry. Disperse 18 kg of water, 3.33 kg of 60 wt% polytetrafluoroethylene emulsion, and 2.5 kg of 10 wt% gum arabic solution for 30 min; add 8.75 kg of a potassium polyacrylate solution containing 250 g of potassium polyacrylate (the number average molecular weight of potassium polyacrylate is 1,250,000) and disperse for 1 h to obtain a viscous solution; slowly add the stirred solid powder. The solid powder composition is 40 kg of nickel hydroxide powder, 4 kg of graphite powder, 1 kg of carbon nanotubes, 2 kg of cobalt hydroxide, and 0.5 kg of zinc powder, and disperse for 2 h to obtain a uniform nickel positive electrode slurry with a viscosity of 9873 mPa s.

[0064] Drawing on the nickel foam substrate: Unroll the nickel foam with a width of 500 mm and a thickness of 1.6 mm, set the pre-pressed thickness of the nickel foam to 1.2 mm, and use four-roll sizing for drawing. The drawing speed is set to 1 m s -1, the nickel positive electrode slurry was evenly drawn and coated on nickel foam. The drying zone is divided into four temperature zones, and the temperatures are set at 80 °C, 100 °C, 120 °C, and 100 °C respectively. After drying, the electrode was rolled. After rolling, the thickness of the positive electrode sheet was 0.7 mm. After rolling, it was sliced into positive electrode sheets with a length of 500 mm, a width of 300 mm, and a thickness of 0.7 mm. After weighing, the mass of the nickel foam was subtracted to obtain the content of the positive electrode active composite in the electrode sheet. Five positive electrode sheets were weighed, and the content of the positive electrode active composite in a single positive electrode sheet was calculated to be 171 ± 0.9 mg cm -2 .

[0065] A zinc-nickel single-flow battery stack composed of 5 single cells was assembled. The negative electrode used carbon felt, the positive electrode was the electrode sheet prepared by the above scheme, the electrolyte was a 7M potassium hydroxide solution dissolved with 0.5M zinc oxide, and a magnetic pump was selected as the power pump. The obtained zinc-nickel single-flow battery stack was tested under a current density of 35 mA cm -2 , charged to 10.1 V and discharged to 4 V. Figure 1 Figure 9 is the mass specific capacity-voltage relationship curve of the zinc-nickel single-flow battery stack of Example 1 at a current density of 35 mA cm -2 . Figure 2 Figure 13 is the cycle efficiency diagram of the zinc-nickel single-flow battery stack of Example 1 at a current density of 35 mA cm -2 . The results of the positive electrode active composite content, the mass specific capacity of the positive electrode sheet, the Coulomb efficiency, and the energy efficiency are shown in Table 1.

[0066] Example 2

[0067] The slurry was prepared using a vacuum mixer. 2 kg of water, 5.42 kg of 60 wt% polytetrafluoroethylene emulsion, and 5 kg of 10 wt% gum arabic solution were dispersed for 100 min; 5 kg of a potassium polyacrylate solution containing 25 g (the number average molecular weight of potassium polyacrylate was 10,000,000) was added and dispersed for 2 h to obtain a viscous solution; the solid powder mixture was slowly added and stirred evenly. The solid powder composition was 33.5 kg of nickel hydroxide, 7.5 kg of graphite powder, and 5 kg of cobaltous oxide, and it was dispersed for 3 h to obtain a nickel positive electrode slurry with a uniform viscosity of 18749 mPa s.

[0068] Drawing on the nickel foam substrate: The nickel foam with a width of 200 mm and a thickness of 2.0 mm was unrolled, the pre-pressed thickness of the nickel foam was set to 1.5 mm, and four-roll sizing was used for drawing. The drawing speed was set at 0.5 m s -1, the nickel positive electrode slurry was evenly drawn and coated on nickel foam. The drying zone was divided into four temperature zones, and the temperatures were set at 90 °C, 110 °C, 130 °C, and 120 °C respectively. After drying, the electrode was rolled. After rolling, the thickness of the positive electrode sheet was 1.00 mm. After rolling, it was sliced into positive electrode sheets with a length of 300 mm, a width of 200 mm, and a thickness of 1.00 mm. After weighing, the mass of the nickel foam was subtracted to obtain the content of the positive electrode active complex in the electrode. Five positive electrode sheets were weighed, and the content of the positive electrode active complex in a single positive electrode sheet was calculated to be 231 ± 1.4 mg cm -2 .

[0069] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The cyclic efficiency diagram of Example 2 obtained was similar to that of Example 1. The results of the content of the positive electrode active complex, the mass specific capacity of the positive electrode sheet, the Coulomb efficiency, and the energy efficiency are shown in Table 1.

[0070] Example 3

[0071] A vacuum mixer was used for slurry preparation. 35 kg of water, 10 kg of ethanol, and 2.5 kg of 60 wt% polytetrafluoroethylene emulsion were dispersed for 10 min; 25 kg of a potassium polyacrylate solution with a solid content of 2 kg (the number average molecular weight of potassium polyacrylate was 5000) was added and dispersed for 30 min to obtain a viscous solution; the solid powder mixture, which consisted of 43 kg of nickel hydroxide powder, 1.5 kg of conductive carbon black, 1 kg of graphene, 0.5 kg of cobalt oxide, and 0.5 kg of zinc powder, was slowly added and stirred for 90 min to obtain a uniform nickel positive electrode slurry with a viscosity of 3541 mPa s.

[0072] Drawing of nickel foam substrate: The 400-mm-wide and 1.6-mm-thick nickel foam was unrolled, and the pre-pressed thickness of the nickel foam was set at 1.0 mm. Four-roll sizing was used for drawing, and the drawing speed was set at 2.5 m s -1 , and the nickel positive electrode slurry was evenly drawn and coated on the nickel foam. The drying zone was divided into four temperature zones, and the temperatures were set at 70 °C, 90 °C, 100 °C, and 90 °C respectively. After drying, the electrode was rolled. After rolling, the thickness of the positive electrode sheet was 0.5 mm. After rolling, it was sliced into positive electrode sheets with a length of 400 mm, a width of 300 mm, and a thickness of 0.5 mm. After weighing, the mass of the nickel foam was subtracted to obtain the content of the positive electrode active complex in the electrode. Five positive electrode sheets were weighed, and the content of the positive electrode active complex in a single positive electrode sheet was calculated to be 130 ± 0.7 mg cm -2 .

[0073] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The cyclic efficiency diagram of Example 3 obtained was similar to that of Example 1. The results of the content of the positive electrode active complex, the mass specific capacity of the positive electrode sheet, the Coulomb efficiency, and the energy efficiency are shown in Table 1.

[0074] Example 4

[0075] The preparation method of the positive electrode sheet is the same as that of Example 1, except that in the potassium polyacrylate solution with the same mass added, it contains 125 g of potassium polyacrylate with a number-average molecular weight of 100,000 and 125 g of potassium polyacrylate with a number-average molecular weight of 3,000,000.

[0076] The zinc-nickel single-flow battery stack is assembled and the battery performance is tested using the same method as in Example 1. The cyclic efficiency diagram of Example 4 obtained is similar to that of Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulomb efficiency, and the energy efficiency are shown in Table 1.

[0077] Example 5

[0078] The preparation method of the nickel positive electrode material is the same as that of Example 1, except that in the potassium polyacrylate solution with the same mass added, it contains 50 g of potassium polyacrylate with a number-average molecular weight of 50,000 and 200 g of potassium polyacrylate with a number-average molecular weight of 500,000.

[0079] The zinc-nickel single-flow battery stack is assembled and the battery performance is tested using the same method as in Example 1. The cyclic efficiency diagram of Example 5 obtained is similar to that of Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulomb efficiency, and the energy efficiency are shown in Table 1.

[0080] Example 6

[0081] The preparation method of the nickel positive electrode material is the same as that of Example 1, except that in the potassium polyacrylate solution with the same mass added, it contains 200 g of potassium polyacrylate with a number-average molecular weight of 10,000 and 50 g of potassium polyacrylate with a number-average molecular weight of 5,000,000.

[0082] The zinc-nickel single-flow battery stack is assembled and the battery performance is tested using the same method as in Example 1. The cyclic efficiency diagram of Example 6 obtained is similar to that of Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulomb efficiency, and the energy efficiency are shown in Table 1.

[0083] Example 7

[0084] The preparation scheme of the positive electrode paste is the same as that of Example 3.

[0085] The preparation method of the nickel positive electrode material is the same as that of Example 1, except that the drying temperatures in the four zones are set to 70 °C, 90 °C, 100 °C, and 90 °C respectively.

[0086] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The cyclic efficiency graph of Example 7 obtained was similar to that of Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulombic efficiency, and the energy efficiency are shown in Table 1.

[0087] Example 8

[0088] The preparation method of the nickel positive electrode material was the same as that in Example 1, except that the drying temperatures in the four zones were set to 90 °C, 110 °C, 130 °C, and 120 °C, respectively.

[0089] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The cyclic efficiency graph of Example 8 obtained was similar to that of Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulombic efficiency, and the energy efficiency are shown in Table 1.

[0090] Example 9

[0091] The preparation method of the nickel positive electrode material was the same as that in Example 1, except that the dried electrode sheet was roll-pressed to 0.5 mm.

[0092] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The cyclic efficiency graph of Example 9 obtained was similar to that of Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulombic efficiency, and the energy efficiency are shown in Table 1.

[0093] Example 10

[0094] The preparation method of the nickel positive electrode material was the same as that in Example 1, except that the dried electrode sheet was roll-pressed to 1.0 mm.

[0095] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The cyclic efficiency graph of Example 10 obtained was similar to that of Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulombic efficiency, and the energy efficiency are shown in Table 1.

[0096] Example 11

[0097] The preparation method of the nickel positive electrode material was the same as that in Example 1, except that the pre-pressed thickness of the nickel foam was set to 1.0 mm.

[0098] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The cyclic efficiency graph of Example 11 obtained was similar to that of Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulombic efficiency, and the energy efficiency are shown in Table 1.

[0099] Comparative Example 1

[0100] The preparation method of the nickel positive electrode material is the same as that of Example 1, except that 8.75 kg of a potassium polyacrylate solution containing 250 g of potassium polyacrylate (the number average molecular weight of potassium polyacrylate is 1,250,000) is added and changed to 8.75 kg of a sodium carboxymethyl cellulose solution containing 250 g of sodium carboxymethyl cellulose.

[0101] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The cycle efficiency diagram of Comparative Example 1 is shown in Figure 3 , and the results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulomb efficiency, and the energy efficiency are shown in Table 1. It can be seen from Figure 3 that the energy efficiency of the zinc-nickel single-flow battery stack assembled with the positive electrode using sodium carboxymethyl cellulose as a thickener is lower than 70%, and the attenuation is obvious. The main reason is that sodium carboxymethyl cellulose is unstable in a strong alkaline solution, and the scouring of the flowing electrolyte in the zinc-nickel single-flow battery stack on the electrode further aggravates the collapse of the electrode skeleton, resulting in serious shedding of the positive electrode powder in a short time, which is not suitable for the zinc-nickel single-flow battery system.

[0102] Comparative Example 2

[0103] The preparation method of the nickel positive electrode is the same as that of Example 1, except that 8.75 kg of a potassium polyacrylate solution is added and changed to 8.75 kg of water.

[0104] The zinc-nickel single-flow battery stack was assembled and the battery performance was tested using the same method as in Example 1. The results of the positive electrode active complex content, the mass specific capacity of the positive electrode sheet, the Coulomb efficiency, and the energy efficiency are shown in Table 1. The slurry prepared without adding potassium polyacrylate in Comparative Example 2 has obvious particle sense, poor slurry consistency, and poor performance of the prepared nickel positive electrode.

[0105] Comparative Example 3

[0106] The preparation method of the nickel positive electrode is the same as that of Example 1, except that the same mass of potassium polyacrylate solution containing 250 g of potassium polyacrylate (the number average molecular weight of potassium polyacrylate is 1,250,000) is added. The viscosity of the obtained nickel positive electrode slurry is too high to penetrate into the nickel foam substrate, and the foam-type nickel positive electrode required by the present invention cannot be obtained.

[0107] Table 1

[0108]

[0109]

[0110] As can be seen from the results in Table 1, the positive electrodes prepared by the embodiments of the present invention have good consistency and stability, achieving batch production of zinc-nickel single-flow battery slitting positive electrode sheets with a width of 500 mm. The production process is rigorous, with good consistency, low energy consumption, and high production efficiency. At the same time, the positive electrodes prepared in batches are assembled into zinc-nickel single-flow battery stacks to achieve high Coulombic efficiency and high energy efficiency.

[0111] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.

Claims

1. A zinc-nickel single-flow battery slurry positive electrode sheet, comprising a nickel foam substrate and a positive electrode active composite distributed in the nickel foam substrate, characterized in that: The positive electrode active composite comprises a positive electrode active material, a conductive agent, potassium polyacrylate and a binder, wherein the content of potassium polyacrylate in the positive electrode active composite is 0.01-4.00 wt %.

2. The positive electrode sheet according to claim 1, wherein: The width of the positive electrode sheet can reach 500mm; and / or The thickness of the positive electrode sheet is 0.5 to 1.0 mm; and / or In the positive electrode sheet, the loading amount of positive electrode active material is 0.10-0.25 g cm -2 .

3. The positive electrode sheet according to claim 1 or 2, wherein: In the positive electrode active composite, The number average molecular weight of potassium polyacrylate is 5000-10000000, preferably the potassium polyacrylate comprises potassium polyacrylate with a number average molecular weight of 10000-100000 and potassium polyacrylate with a number average molecular weight of 500000-5000000, and the mass content of the two is not less than 15wt% respectively, preferably 20-80wt% respectively, based on the total weight of potassium polyacrylate; and / or The content of potassium polyacrylate is 0.05-4.00wt%; and / or The positive electrode active material content is 60 to 95 wt%, preferably 65 to 90 wt%; and / or Conductive agent 3-20wt%, preferably 5-16wt%; and / or Binder 1-10wt%, preferably 2-8wt%; Preferably, The positive electrode active composite contains a positive electrode active additive, and the additive is selected from one or more of cobalt hydroxide, cobaltous oxide, manganese dioxide, and zinc powder, preferably cobalt hydroxide and zinc powder; More preferably, in the positive electrode active composite, the content of the positive electrode active additive is 1 to 15 wt %, preferably 2 to 11 wt %.

4. A method for preparing a zinc-nickel single-flow battery slurry positive electrode sheet, characterized in that: The method comprises: positive electrode active compound preparation, positive electrode slurry mixing, foam nickel substrate slurry pulling, drying, rolling and slicing. The positive electrode active compound preparation contains positive electrode active material, conductive agent, potassium polyacrylate and adhesive. The content of potassium polyacrylate in the positive electrode active compound is 0.01-4.00wt%.

5. The method according to claim 4, wherein: In the positive electrode active composite ingredients, The number average molecular weight of potassium polyacrylate is 5000-10000000, preferably the potassium polyacrylate comprises potassium polyacrylate with a number average molecular weight of 10000-100000 and potassium polyacrylate with a number average molecular weight of 500000-5000000, and the mass content of the two is not less than 15wt% respectively, based on the total weight of potassium polyacrylate; and / or The content of potassium polyacrylate is 0.05-4.00wt%; and / or The positive electrode active material content is 60 to 95 wt%, preferably 65 to 90 wt%; and / or Conductive agent 3-20wt%, preferably 5-16wt%; and / or Binder 1-10wt%, preferably 2-8wt%; Preferably, The positive electrode active composite contains a positive electrode active additive, and the additive is selected from one or more of cobalt hydroxide, cobaltous oxide, manganese dioxide, and zinc powder, preferably cobalt hydroxide and zinc powder; More preferably, in the positive electrode active composite, the content of the positive electrode active additive is 1 to 15 wt %, preferably 2 to 11 wt %.

6. The method according to claim 4 or 5, wherein: The positive electrode slurry mixing process includes: adding positive electrode active composites into a solvent, and mixing them evenly to obtain positive electrode slurry; Preferably, In the positive electrode slurry, the mass concentration of the positive electrode active composite is 40 to 80 wt %, and the mass concentration of the solvent is 20 to 60 wt %; and / or The solvent is selected from one or more of water, ethanol, and isopropanol, preferably a mixed solution of isopropanol and water, and the amount of isopropanol is 5-15wt% based on the total weight of the solvent; and / or The viscosity of the positive electrode slurry is 3000 to 20000 mPa s.

7. The method according to any one of claims 4 to 6, wherein: The foam nickel substrate slurry drawing process includes: unwinding, pre-pressing, and slurry drawing; Preferably, During the unwinding process, a nickel foam coil with a width not exceeding 500 mm and a thickness not less than 1.6 mm is placed; and / or The pre-pressed thickness of the nickel foam substrate is set to 1.0 to 1.5 mm; and / or The slurry is drawn using four rollers; and / or The pulling speed is set to 0.5~3m s -1 ; and / or During the drying process: four temperature zones are set for drying, and the temperatures of the four temperature zones are 70-90°C, 90-110°C, 100-130°C, and 80-120°C respectively; and / or After rolling, the thickness of the positive electrode sheet is 0.5 to 1.0 mm.

8. A zinc-nickel single-flow battery slurry positive electrode sheet prepared by the method according to any one of claims 4 to 7.

9. A zinc-nickel single-flow battery, characterized in that: The positive electrode is a zinc-nickel single-flow battery slurry positive electrode sheet as claimed in any one of claims 1 to 3 and 8, wherein the positive electrode sheet comprises a nickel foam substrate and a positive electrode active composite distributed in the nickel foam substrate, wherein the positive electrode active composite comprises a positive electrode active material, a conductive agent, potassium polyacrylate and a binder, wherein the content of potassium polyacrylate in the positive electrode active composite is 0.01 to 4.00 wt%; Preferably, the negative electrode is selected from one or more of carbon felt, graphite felt, carbon cloth or zinc sheet, the electrolyte is a 7-10M potassium hydroxide solution containing 0.5-1M zinc oxide, and the power pump is selected from a magnetic pump.

10. A zinc-nickel single-flow battery stack, characterized in that: The zinc-nickel single-flow battery stack is assembled by connecting 5 to 40 zinc-nickel single-flow batteries according to claim 9 in series.